The THE IMPLEMENTATION OF THEME-BASED TEACHING TO IMPROVE STUDENTS’ ENGLISH VOCABULARY IN SPEAKING - Fitrah Rachmadani; Erwin akib; Eka Prabawati rum (FKIP Unismuh Makassar, 2022)
The objective of the research was to discover whether or not the theme-based teaching improve students’ vocabulary in speaking skill. This research was in quantitative design. The population of this research was 100 students in MTS Muhammadiyah Lempangan Gowa at VII grade. By applying simple random sampling technique, the sample of this research was 30 students of class VII-A. Research instruments used for collecting the data were pretests and posttest. The research was done in two cycles. The pretest consisted of six questions. The post test 1 consisted of one question with theme “school”. The post test 2 consisted of the similar instruction as the prior test but modified with pictures. The results of the research showed that the students' vocabulary mastery in speaking skill increased significantly. In pretest, there were only 14 students fulfill the KKM which was 70. The mean score of pretest was 68.3. In cycle 1, the mean score kept improving to 73.05 came from 21 students. In cycle 2, the mean score rose to 79.56 resulted from 24 students. There was 4 student left who did not pass the KKM.